Role of Age, Sex, and Body Mass Index on Blood Pressure among Students of St. Hendrikus High School, Surabaya, Indonesia - Andajani, Susilowati (Folia Medica Indonesiana, 2020)
The purpose of this study was to analyze the influence of age, sex, Body Mass Index (BMI), and nutritional status on blood pressure in class X and XI students, SMAK St. Hendrikus, Surabaya, Indonesia. The sample of students in class X and XI of SMAK St. Hendrikus Surabaya in 2013. The sample size was 150 students. The sampling technique was consecutive sampling. The independent variables were age, sex, BMI, and nutritional status, while the dependent variable was blood pressure. Data were analyzed by Pearson correlation test, Spearman, and Chi Square statistical test with ?=0.05. The level of risk was calculated by epi info program. Most students (40.7%) were 16 years old, those with pre-hypertension (systolic) 26.7%, grade 1 systolic hypertension by 1.3%, diastolic pre-hypertension 25.3% and grade 1 diastolic hypertension by 6.7%. Age did not have significant influence (p=0.623) on systolic blood pressure, but had a significant influence (p=0.002) on diastolic blood pressure. Male sex significantly influenced systolic (p=0.002, RR 5.36 95% CI 2.2320-12.8649) and diastolic (p <0.001, RR 1.95 95% CI 1.1272-3 , 3719) blood pressure. BMI had significant influence (p <0.001) on blood pressure. Nutritional status had significant influence on systolic blood pressure (p=0.002), with overnutrition status with RR 2.28, 95% CI 1.3983-3.7104. Nutritional status had significant influence on diastolic blood pressure (p <0.001), and with overnutrition status with RR 2.73, 95% CI 1.8143-4.1179. In conclusion, the trend for pre-hypertension to grade 1 diastolic hypertension increases with age and age has an influence on diastolic blood pressure. The risk of males to have pre-hypertension to grade 1 systolic hypertension is 5.36 times that of females, and the risk to have pre-hypertension to grade 1 diastolic hypertension is 1.95 times that of women. The higher the BMI, the higher the systolic and/or diastolic blood pressure.